HEALTH EDUCATION AND TRAINING FOR ADOLESCENT GIRLS IN FACING MENARCHE - Umi Narsih; Homsiatur Rohmatin; Agustina Widayati (International Journal of Engagement and Empowerment, 2022)
Women's physical growth and biological maturity, including menarche, are influenced by their level of happiness. This can have an effect on adolescent girls' readiness to face menarche. The consequences include exposing adolescent girls to unwanted problems such as depression, smoking, eating disorders, mental disorders, and reproductive organ infections. The goal of this community service is to educate and train adolescent girls at MI Darul Ulum Kraksaan in Probolinggo, East Java, Indonesia on how to prepare for menarche. A peer group method was used in collaboration with the Principal of MI Darul Ulum Kraksaan. This activity drew 40 adolescent girls ranging in age from 9 to 13 years. The results of community service activities informed that after health educating and training, the adolescent girls of MI Darul Ulum now they have a positive response to menarche such as not feeling ashamed, anxious, or afraid, and being ready to face menarche. Adolescent girls' readiness to face menarche has a positive impact on vulva hygiene behavior and reduces the risk of contracting HIV